Las especies de Coccus que afectan Coffea Arabica en Brasil (Coccoidea: Coccidae) y redescripción de dos especies - Granara, Maria Cristina (2010)
Five Coccus on Coffea arabica from the states of Bahia, Espírito Santo and Minas Gerais were studied. Females were prepared and mounted in Canada balsam. Coccus brasiliensis Fonseca and Coccus lizeri (Fonseca) were redescribed and Coccus alpinus De Lotto, Coccus celatus De Lotto and Coccus viridis (Green) were characterized. A key to species and illustration of all of them are included. Coccus alpinus and C. celatus are new records for Brazil and the Neotropical Region.